2010
DOI: 10.1097/iae.0b013e3181e09739
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Hemorrhagic Complications After Intravitreal Bevacizumab (Avastin) or Ranibizumab (Lucentis) Injections on Systemically Anticoagulated Patients

Abstract: The risk of hemorrhagic complications in systemically anticoagulated patients receiving intravitreal injections is extremely low. Because of the demonstrated thromboembolic risk of stopping anticoagulant therapy, we recommend that patients continue their current regiment without cessation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 22 publications
2
15
0
1
Order By: Relevance
“…Substantial intraocular hemorrhages can cause severe visual acuity impairment, and in some cases, surgery is needed for complete resolution. 20,21 Unfortunately, there are no substantial recommendations or guidelines regarding the modification of warfarin and NOACs prior to any type of ocular surgery. The decision to withhold, modify, or continue anticoagulation should be individualized.…”
Section: Discussionmentioning
confidence: 99%
“…Substantial intraocular hemorrhages can cause severe visual acuity impairment, and in some cases, surgery is needed for complete resolution. 20,21 Unfortunately, there are no substantial recommendations or guidelines regarding the modification of warfarin and NOACs prior to any type of ocular surgery. The decision to withhold, modify, or continue anticoagulation should be individualized.…”
Section: Discussionmentioning
confidence: 99%
“…37,38 In patients who were under treatment with anticoagulants, no new intraocular hemorrhages or other hemorrhagic complications were reported. 39,40 Considering the increased risk of thromboembolic events after stopping anticoagulant therapy, discontinuation of the anticoagulants for intravitreal injections is not recommended. 40 Systemic safety Anti-VEGF agents are used widely in treatment protocols of many solid cancers.…”
Section: Methodsmentioning
confidence: 99%
“…39,40 Considering the increased risk of thromboembolic events after stopping anticoagulant therapy, discontinuation of the anticoagulants for intravitreal injections is not recommended. 40 Systemic safety Anti-VEGF agents are used widely in treatment protocols of many solid cancers. Several adverse events have been reported with the systemic administration of anti-VEGF monoclonal antibodies, including thromboembolic events, myocardial infarction, stroke, hypertension, gastrointestinal perforations, and kidney disease.…”
Section: Methodsmentioning
confidence: 99%
“…[9][10][11] Kiernan et al reported that both systemic Plavix and Coumadin use were significantly associated with an increased risk for the development of intraocular hemorrhage in subjects with neovascular AMD. 9 However, Mason et al reported that the risk of hemorrhagic complications in systemically anticoagulated subjects receiving intravitreal injections is extremely low.…”
Section: Discussionmentioning
confidence: 97%
“…8 With the exception of systemic anticoagulation, there is little information regarding the systemic and ocular risk factors for submacular hemorrhage after IVR. [9][10][11] The aim of this study is to report the incidence of and risk factors for macular hemorrhage after IVR for neovascular AMD. neovascular AMD between 1 June 2009 and 30 June 2010 were included.…”
Section: Introductionmentioning
confidence: 99%